2017
DOI: 10.1107/s205698901701355x
|View full text |Cite
|
Sign up to set email alerts
|

MIn(HAsO4)2(M= K, Rb, Cs): three new hydrogenarsenates adopting two different structure types

Abstract: Potassium indium bis[hydrogen arsenate(V)], KIn(HAsO 4 ) 2 , rubidium indium bis[hydrogen arsenate(V)], RbIn(HAsO 4 ) 2 , and caesium indium bis[hydrogen arsenate(V)], CsIn(HAsO 4 ) 2 , were grown under mild hydrothermal conditions (T = 493 K, 7-8 d). KIn(HAsO 4 ) 2 adopts the KSc(HAsO 4 ) 2 structure type (space group C2/c), while RbIn(HAsO 4 ) 2 and CsIn(HAsO 4 ) 2 crystallize in the space group R3c and are the first arsenate representatives of the RbFe(HPO 4 ) 2 structure type. All three compounds have tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…Since application of the appropriate twin matrices did not improve the refinement and no O ligands were found for this position, it was omitted from the refinement. A very similar situation SEM micrographs of hydrothermally synthesized crystals of (a) -RbAl-(HAsO 4 ) 2 , (b) -CsFe(HAsO 4 ) 2 , (c) -CsFe(HAsO 4 ) 2 and (d) CsFe 2 -As(HAsO 4 ) 6 was encountered for isotypic -CsIn(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2017d).…”
Section: Structure Determination and Refinementsupporting
confidence: 53%
See 1 more Smart Citation
“…Since application of the appropriate twin matrices did not improve the refinement and no O ligands were found for this position, it was omitted from the refinement. A very similar situation SEM micrographs of hydrothermally synthesized crystals of (a) -RbAl-(HAsO 4 ) 2 , (b) -CsFe(HAsO 4 ) 2 , (c) -CsFe(HAsO 4 ) 2 and (d) CsFe 2 -As(HAsO 4 ) 6 was encountered for isotypic -CsIn(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2017d).…”
Section: Structure Determination and Refinementsupporting
confidence: 53%
“…Among the many different structure types found during that study, one atomic arrangement, the RbFe(HPO 4 ) 2 -type (Lii & Wu, 1994), was found to be extremely versatile and allowed the incorporation of a wide variety of cations. Two new representatives of this structure type, which was previously also known for RbM 3+ (HPO 4 ) 2 (M 3+ = Al, Ga; Lesage et al, 2007), M + In(HAsO 4 ) 2 (M + = Rb, Cs; Schwendtner & Kolitsch, 2017d) and RbFe(HAsO 4 ) 2 (Schwendtner & Kolitsch, 2018), are presented in this study, namely RbAl(HAsO 4 ) 2 and CsFe(HAsO 4 ) 2 . Two chemically identical compounds, crystallizing in the space group R32, represent a novel but closely related structure type.…”
Section: Introductionmentioning
confidence: 72%
“…The unitcell parameters a and V correlate well with the size of both cations, but the influence of the M + cations is stronger. It seems that in order to incorporate the small AsO 6 octahedron in the structure the cell widens along the a axis to incorporate the large M + cations and is strongly compressed along c. This effect is also visible in the hydrogen bonds that are very strong in the RbFe(HPO 4 ) 2 -type arsenates with D-HÁ Á ÁA bond lengths ranging from 2.598 (2) to 2.634 (2) Å , while for the RbAl 2 As(HAsO 4 ) 6 -type arsenates they range from 2.727 (2) to 2.7481 (19) Å (Schwendtner & Kolitsch, 2017b, 2018athis paper).…”
Section: Figurementioning
confidence: 94%
“…One atomic arrangement, the RbFe(HPO 4 ) 2 type (Lii & Wu, 1994;rhombohedral, R3c), and its two relatives, the CsAl 2 As-(HAsO 4 ) 6 type (Schwendtner & Kolitsch, 2018a, rhombohedral, R3c) and the RbAl(HAsO 4 ) 2 type (Schwendtner & Kolitsch, 2018a, rhombohedral, R32), were found to exhibit a large crystal-chemical flexibility, which allows the incorporation of a wide variety of M + and M 3+ cations. So far the RbFe(HPO 4 ) 2 -type is represented by eight arsenate members with the following M + M 3+ combinations: TlAl, (NH 4 )Ga, RbIn, RbGa, RbAl, RbFe, CsIn and CsFe (Schwendtner & Kolitsch, 2017b, 2018a. Six arsenates of the CsAl 2 As-(HAsO 4 ) 6 type are known with the following M + M 3+ combinations: RbGa, CsGa, TlGa, RbAl, CsAl and CsFe (Schwendtner & Kolitsch, 2018a,c,d).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The refinement of CsGa(HAsO 4 ) 2 revealed a considerable residual electron-density peak of 5.1 e Å À3 1.27 Å away from As and 1.62 Å away from the O1 site. The corresponding position can be generated by a mirror plane in (110) and therefore was assumed to be an alternative flipped As position (sharing the same O1 atom), similar to what was encountered in related TlAl(HAsO 4 ) and CsIn(HAsO 4 ) 2 (R3c type; Schwendtner & Kolitsch, 2017b). An inclusion of the alternative position led to a considerable drop in the conventional R factor and weight parameters and the highest residual electron densities also decreased considerably.…”
Section: Refinementmentioning
confidence: 99%